2021
DOI: 10.1200/jco.20.03007
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Tool Integrating the 21-Gene Recurrence Score and Clinical-Pathological Features to Individualize Prognosis and Prediction of Chemotherapy Benefit in Early Breast Cancer

Abstract: PURPOSE The 21-gene recurrence score (RS) is prognostic for distant recurrence (DR) and predictive for chemotherapy benefit in early breast cancer, whereas clinical-pathological factors are only prognostic. Integration of genomic and clinical features offers the potential to guide adjuvant chemotherapy use with greater precision. METHODS We developed a new tool (RSClin) that integrates RS with tumor grade, tumor size, and age using a patient-specific meta-analysis including 10,004 women with hormone receptor–p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 18 publications
1
83
0
2
Order By: Relevance
“…The 95-gene signature classi cation was not signi cant among patients aged ≤ 50 years, which may be attributable to the small sample size of that population. Recently, Sparano et al showed that a new tool (RSCline), which integrates the 21-gene recurrence score and the clinicopathological features of histologic tumor grade, tumor size, and patient age at surgery, could provide more individualized estimation of survival bene t from adding adjuvant chemotherapy to endocrine therapy [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 95-gene signature classi cation was not signi cant among patients aged ≤ 50 years, which may be attributable to the small sample size of that population. Recently, Sparano et al showed that a new tool (RSCline), which integrates the 21-gene recurrence score and the clinicopathological features of histologic tumor grade, tumor size, and patient age at surgery, could provide more individualized estimation of survival bene t from adding adjuvant chemotherapy to endocrine therapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Time to recurrence (TTR) analysis TTR curve for patients with tumors classi ed as 95GC-L and as 95GC-H for populations with "intermediate" 21-gene signature assay RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Time to recurrence (TTR) analysis TTR curve for patients with tumors classi ed as 95GC-L and as 95GC-H for populations with "intermediate" 21-gene signature assay RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the RS score was found to show different values of predicting the bene t of adding chemotherapy in subsets of different ages. The Trial Assigning Individualized Options for Treatment (TAILORx) categorized RS ranges as low-(< 11), intermediate- (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) or high-(> 25) risk subgroups and discovered that for the majority of population with RS < 25, endocrine therapy alone was noninferior to combined chemo-endocrine therapy. Of note, the interaction between age and RS was obvious.…”
Section: Introductionmentioning
confidence: 99%